Implementation of Bayani Method in Memorizing Al-Qur'an at School of Hafidz Qur'an of Al-Islam Lamongan - Tsania Rosyidah Hasna (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
This study aims to discuss how the implementation of the Bayani method in memorizing the Qur'an at School of Hafidz Qur'an al-Islam Lamongan. what are the inhibiting and supporting factors, and how are the solutions to overcome these obstacles. This type of research in this study uses field research, with a qualitative approach; Data collection methods: observation, interviews, and documentation. The research findings in this study can be concluded: first: Implementation of the Bayani method in memorizing the Qur'an at School of Hafidz Qur'an al-Islam Lamongan was carried out in four stages: preparation, apperception, material, evaluation and closing .; second: supporting factors for the implementation of the Bayani method in memorizing the Qur'an in School of Hafidz Qur'an al-Islam Lamongan namely the presence of adequate facilities, usis santri are productive age, instructors according to their fields, guidance of the Ustadz / dzah, quiet environment, the formation Santri's guardian forum, as well as regular meetings. the inhibiting factors were, the students had difficulty managing time, the lack of awareness of the benefits of the Bayani method, the santri were partially not fluent in reading the Qur'an, as well as the lack of support from the trustees of the students; third: the solution to overcome these obstacles is to give the task of memorizing at home, set an example of the Qur'an tadarrus, encourage students to enter TPQ, establish communication with the guardians of students. Keywords: Bayani Method, Memorizing Al Qur'an, Implementation